RAMIFICATION IN DENTAL PRACTICE WITH THE KNOWLEDGE ANDAWARENESS IN THE SUBJECT OF TOOTH MORPHOLOGY - Namerah Qamar et al (Baqai Journal of Health Sciences)
Background:The concept of assessing that, the knowledge and awareness of the subject of tooth morphology among the final year BDS students and house officers is helpful in their clinical practice. Methodology:The study was conducted among the final year BDS students and house officers. Data was collected by a predesigned proforma. The sample size calculated was 310 by keeping proportion 52% and confidence interval 95% and margin of error 5% in open epi. 3.01. Results:Results of the survey and feedback revealed that the technical difficulties had been faced during clinical practice in different fields of dentistry due to the lack of basic knowledge of the subject. Conclusion:Knowledge and awareness of the subject lays the foundation headed for a skillful dentist and an assertive clinician.